A LITERARY REVIEW OF SIDDHA TREATMENT FOR MECHANICAL TRAUMA - M, JENIFER VIMALA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Siddha is one of the oldest traditional medical systems followed in the Southern part of India. Herbal medicines and their preparation for the wound healing in mechanical trauma are found in Siddha texts. Mechanical trauma is an injury or wound to a living body caused by the application of external force or violence. Both internal and external medications used for the treatment of mechanical trauma were collected and compiled from this work. The treatment for specific wounds such as abrasion, burns and scalds, contusion, incision, and lacerated wounds in mechanical trauma is briefly discussed in this work. Of these, even simple herbs were used to arrest bleeding from wounds and also cures severe wounds are noteworthy. From the literary evidences, it is clear that ancient people used the medicinal plants and their resources in the treatment and management of mechanical trauma as the first hand medicine. This work paves the way for the future researchers to concentrate on mechanism of action of these medications for its specific role in wound healing will strengthen our Siddha system.